2015
DOI: 10.1108/jsocm-03-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

The credibility of refutation in two-sided anti-drug messages

Abstract: Purpose – This study aims to address the credibility effects of refutational versus non-refutational two-sided messages. Additionally, it aims to unravel the moderating role of issue ambivalence and argument type. Design/methodology/approach – A 2 × 2 × 2 between-subjects factorial experimental design (N = 853 adolescents) investigates the effect of eight anti-binge drinking and anti-marijuana messages on source and message credibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The assertion of Eisend (2006) is still valid, that is, knowledge of the effectiveness of 2SMs, and of the influences of potential moderating and mediating variables, are valuable to marketers in showing how communication strategies aimed at consumers can be improved. However, there is a lack of research into the persuasive impact of 2SMs (Cornelis et al, 2015). Therefore, this research seeks to clarify how 2SMs work by explaining their causal effects on purchase intention, moderated by the self-confidence of individuals, and to examine the underlying mechanisms by which 2SMs are processed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assertion of Eisend (2006) is still valid, that is, knowledge of the effectiveness of 2SMs, and of the influences of potential moderating and mediating variables, are valuable to marketers in showing how communication strategies aimed at consumers can be improved. However, there is a lack of research into the persuasive impact of 2SMs (Cornelis et al, 2015). Therefore, this research seeks to clarify how 2SMs work by explaining their causal effects on purchase intention, moderated by the self-confidence of individuals, and to examine the underlying mechanisms by which 2SMs are processed.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts to model and interpret the effect of 2SMs (Bohner et al, 2003; Chen, 2016; Cornelis et al, 2014, 2015; Eisend, 2007, 2008, 2010; Hastak & Park, 1990; Hunt et al, 1982; Kamins & Marks, 1987; Kao, 2011; Pizzutti et al, 2016; Trifts & Häubl, 2003). However, the diversity of the results, as highlighted by Eisend (2006), indicates the necessity of further research on moderating variables (Cornelis et al, 2015). Moreover, in the context of decision-making, moderators of negative information about the attributes of a product remain largely unexplored (Hair & Bond, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there have been several attempts to model and interpret the effect of 2SMs [3][4][5][6][7][8][9][14][15][16][17][18]. Nonetheless, the heterogeneity of the results, as pointed out by [9], still indicates the need for further investigation of substantive moderating variables [16]. In this research, it is proposed that the effect of 2SMs in online environments could be different from their effect in traditional advertising media.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review identified a strand of theoretical development in the study of the effect of 2SMs, namely to establish the limits of the effect of 2SMs by analyzing how the effect occurs in different situations (e.g., online environments such as social networks and websites). In this regard, there have been several attempts to model and interpret the effect of 2SMs [3][4][5][6][7][8][9][14][15][16][17][18]. Nonetheless, the heterogeneity of the results, as pointed out by [9], still indicates the need for further investigation of substantive moderating variables [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation